Imagine invent program share: a library-hosted computer club promotes 21st-Century literacy skills. - Myers B (Computers in Libraries, 2009)
Bridging the literacy gap will require that we re-evaluate our perspectives and reinvent our practices to better prepare our youth for fully participatory lives in the years ahead.